Interface synthesis for controllable construction of 2D Zn(Bim)(OAc) nanosheets via oil/water system and their application in oil. Issue 5 (6th January 2021) - Wang, Fei-Fei; Ding, Haiyang; Tan, Guang; Liu, Zan; Cheng, Zhi-Lin
Abstract : Fabrication of 2D Zn(Bim)(OAc) MOFs-structured nanosheets based on the oil/water interface. Abstract : The aim of this work was to develop a novel interface synthesis for 2D Zn(Bim)(OAc) nanosheets via an oil/water system. This method involved a two immiscible base oil/water phase system, i.e., one of the initial raw materials (metal salt) was scattered in the base oil phase and the other (organic ligand) was dissolved in the water phase. The results revealed that the 2D Zn(Bim)(OAc) nanosheets, with uniform thickness, were formed at the interface between oil and water. A series of characterization techniques were adopted to determine the structure and composition of the so-formed 2D Zn(Bim)(OAc) nanosheets. Furthermore, the preferred organic interface and the formed 2D-layered structure of 2D Zn(Bim)(OAc) nanosheets showed potential in resolving the dispersion and stability issues of the underlying friction reducing additive in oil. Through the comparative analyses of the dispersion and stability of 2D Zn(Bim)(OAc) nanosheets in the three oils (base oil, castor oil, and grease), the interface interaction between Zn(Bim)(OAc) and oil was extensively discussed.